The Implementation of the Project Based Learning (PjBL) Model to Improve Learning Outcomes and Motivation in the Metamorphosis Topic of Natural Science for Third-Grade Elementary School Students - Wiladati, Sekar Putri; Fitriyeni2, Fitriyeni (The Future of Education Journal, 2025)
In the teaching and learning process, problems are still encountered, such as the low learning motivation of third-grade students, particularly in Natural Science learning. Students tend to show a lack of enthusiasm and motivation during the learning process, which affects their active involvement in class. This study aims to describe the results and learning motivation of third-grade students at SDN 009 Bukit Lembah Subur after implementing the Project-Based Learning (PjBL) model in the metamorphosis topic. The type of research applied in this study is Classroom Action Research, with 21 third-grade students of SDN 009 Bukit Lembah Subur as the subjects. The research instruments used include observation sheets, questionnaires, interview sheets, and test sheets. To analyze the data, the researcher used quantitative data analysis. Based on the research results, it can be concluded that the PjBL model was able to create a more active and meaningful learning environment and encourage student involvement overall. This was reflected in the significant increase in student motivation, from 4 students (20%) showing high motivation in Cycle I to 15 students (72%) in Cycle II. Likewise, the learning outcomes improved, with only 12 students (57%) achieving scores above the minimum competency standard (KKM) in Cycle I, rising to 21 students (100%) in Cycle II.